Immunosuppression mechanism of entomopathogenic bacteria against Galleria mellonella larvae. (June 2019) - Liao, Chunli; Zheng, Mengdong; Chen, Yushou; Wang, Mengjun; Li, Binging
Graphical abstract: Highlights: Immunologic mechanisms on how Enterobacter gergoviae LY2W kills Galleria mellonella were explained. LY2W damaged cellular immunity by breaking down hemocytes and hemolymph. Expressions of two antibacterial peptides, diptericin and drosomycin, were significantly enhanced. LY2W triggered humoral immunity mainly through activating the Toll and Imd pathways. Abstract: Entomopathogenic nematodes (EPNs) and their symbiotic bacteria play a great role in pest bio-control and therefore have been used widely in agricultural production. However, immunologic mechanisms on how they kill their hosts remain little known. Here we investigated the response of cellular immunity to infection by Enterobacter gergoviae LY2W, which is entomopathogenic bacterium of EPN Heterorhabditis megidis 90. Hemocytes started distortion and disintegration after 12 h with a decrease of hemolymph by 34.9%. More interestingly, hemocyte density decreased dramatically to less than 35% of the control at 12 h before larva death. Moreover, the expression of genes coding diptericin and drosomycin responsible for the signaling regulation of humoral immunity indicated that LY2W cells promoted the signaling regulation of humoral immunity mainly by activating Toll and Imd pathways. Therefore, immunosuppression of entomopathogenic bacteria against G. mellonella depended mainly upon disordering the signaling regulation of humoral immunity, destroying hemocyte, and decreasing hemolymph.